The effects of COVID-19 on food equity and nutrition security in sub-Saharan Africa: Lessons from a multi-phase assessment - Salm, Leah; Nisbett, Nick; Lulache, Alexandra (Future Agricultures Consortium, 2022)
The COVID-19 pandemic in sub-Saharan Africa has elicited reactions that are also seen worldwide: widespread and indefinite health effects, and deep reverberations on almost all parts of daily life, from livelihoods, to freedom of movement and the availability of foods and services. As was seen in previous health crises such as that of HIV or Ebola, the effects of the pandemic are mediated by pre-existing power structures, vulnerabilities, and systems of support, which lead to differentiated outcomes for people and communities, often to the detriment of the poorest groups. This study examines the impact of COVID-19 on commercialising farmers across sub-Saharan Africa, with a deeper focus on Nigeria and Malawi, from a food equity perspective.